2013
DOI: 10.1142/s0217979213501622
|View full text |Cite
|
Sign up to set email alerts
|

QUALITATIVE ASPECTS OF THE PHASE DIAGRAM OF J1–J2 MODEL ON THE CUBIC LATTICE

Abstract: The qualitative aspects of the phase diagram of the Ising model on the cubic lattice, with ferromagnetic nearest-neighbor interactions (J 1 ) and antiferromagnetic next-nearest-neighbor couplings (J 2 ) are analyzed in the plane temperature versus α, where α = J 2 /|J 1 | is the frustration parameter.We used the original Wang-Landau sampling and the standard Metropolis algorithm to confront past results of this model obtained by the effective-field theory (EFT) for the cubic lattice. Our numerical results sugg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
(38 reference statements)
2
2
0
4
Order By: Relevance
“…The transition from the superanti ferromagnetic phase to the ferromagnetic one is also a first order phase transition. A similar result was obtained in Monte Carlo numerical simulations in [23], where the critical exponents were calculated in the range of 0 < r < 0.25 and it was demonstrated that this model in such a range belongs to the same univer sality class as the three dimensional classical Ising model. Phase transitions and critical characteristics of the layered antiferromagnetic Ising model in the case of a cubic lattice with next nearest neighbor intralayer interactions are studied in the framework of the Monte Carlo method implementing the replica algorithm.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…The transition from the superanti ferromagnetic phase to the ferromagnetic one is also a first order phase transition. A similar result was obtained in Monte Carlo numerical simulations in [23], where the critical exponents were calculated in the range of 0 < r < 0.25 and it was demonstrated that this model in such a range belongs to the same univer sality class as the three dimensional classical Ising model. Phase transitions and critical characteristics of the layered antiferromagnetic Ising model in the case of a cubic lattice with next nearest neighbor intralayer interactions are studied in the framework of the Monte Carlo method implementing the replica algorithm.…”
Section: Introductionsupporting
confidence: 80%
“…The theoretical analysis and Monte Carlo numeri cal simulations for the Ising model on a cubic lattice with next nearest neighbor interactions were reported in [22,23]. In [22], the authors constructed the phase diagram depicting the dependence of the critical tem perature on the magnitude of the next nearest neigh bor interaction within the range 0 ≤ r ≤ 0.8 of the ratio r = J 2 /J 1 , where J 1 and J 2 are the exchange coupling constants for the nearest and next nearest neighbor interactions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…В качестве примера рассмотрим проблему исследования на простой кубической решетке при учете ферромагнит-ного взаимодействия между ближайшими соседями J 1 и антиферромагнитного взаимодействия между вторыми соседями J 2 в модели Изинга, дискутируемую между авторами работ [18] и [19]. На рис.…”
Section: заключениеunclassified
“…13 приведена фазовая диаграмма из работы [18], на которой при-сутствуют два значения для температуры перехода в точке фрустраций со значением фрустрационного пара-метра α = J 2 /J 1 = 0.25. Главное различие результатов работ [18] и [19] заключается только в нулевом и ненулевом значении этой температуры перехода. При учете эффекта частичного упорядочения можно сделать вывод, что в первом случае должно наблюдаться пони-жение размерности из 3D в 1D, а во втором из 3D в 2D.…”
Section: заключениеunclassified
“…Эта модель является частным случаем модели исследуемой в работах [16,17], когда взаимо-действие следующих ближайших соседей между слоями равно нулю. В работе [14] был рассмотрен случай, когда r = 1.0 (J 1 и J 2 -константы обменного взаимодействия ближайших и следующих за ближайшими соседей соот-ветственно), где r = J 2 /J 1 -величина взаимодействия следующих за ближайшими соседей.…”
Section: Introductionunclassified